2021
DOI: 10.3390/cancers13215259
|View full text |Cite
|
Sign up to set email alerts
|

Photodynamic Priming Improves the Anti-Migratory Activity of Prostaglandin E Receptor 4 Antagonist in Cancer Cells In Vitro

Abstract: The combination of photodynamic agents and biological inhibitors is rapidly gaining attention for its promise and approval in treating advanced cancer. The activity of photodynamic treatment is mainly governed by the formation of reactive oxygen species upon light activation of photosensitizers. Exposure to reactive oxygen species above a threshold dose can induce cellular damage and cancer cell death, while the surviving cancer cells are “photodynamically primed”, or sensitized, to respond better to other dru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 61 publications
0
8
0
Order By: Relevance
“…As a result, effector cells can return to the periphery to eliminate the primary tumor and prevent metastasis. [104,105] This class of therapies is approved by the FDA for cancers such as basal cell skin cancer and non-small cell lung cancer. [106,107] MNAs could provide an alternative to this traditional form of delivery because they target the release of TAAs and adjuvants to APCs in the skin.…”
Section: Photodynamic and Photothermal Therapiesmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, effector cells can return to the periphery to eliminate the primary tumor and prevent metastasis. [104,105] This class of therapies is approved by the FDA for cancers such as basal cell skin cancer and non-small cell lung cancer. [106,107] MNAs could provide an alternative to this traditional form of delivery because they target the release of TAAs and adjuvants to APCs in the skin.…”
Section: Photodynamic and Photothermal Therapiesmentioning
confidence: 99%
“…As a result, effector cells can return to the periphery to eliminate the primary tumor and prevent metastasis. [ 104,105 ] This class of therapies is approved by the FDA for cancers such as basal cell skin cancer and non‐small cell lung cancer. [ 106,107 ]…”
Section: Mnas Are Being Explored To Treat Infectious Cancerous Allerg...mentioning
confidence: 99%
“…Successful application of PDT can lead to the eradication of localized neoplasia without many of the adverse effects associated with chemotherapy and ionizing radiation. Protocols involving combinations of PDT and chemotherapy are also being investigated [ 41 , 42 , 43 ]. The news that yet one more product can catalyze formation of reactive species upon irradiation is of limited interest unless that agent has some unusual properties that are superior to agents already available.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with these dual functions, we and others have shown that PICs targeting the EGFR can attenuate EGFR and extracellular signal-regulated kinases 1/2 (ERK1/2) signaling. 17 , 18 Nonetheless, one of the major challenges associated with PIT is limited photosensitizer delivery to cancer cells. 18 , 19 , 20 This can be attributed to several factors including finite antigen numbers per cancer cell, limited number of photosensitizer-to-antibody payload, and poor tumor accessibility of antibodies.…”
Section: Introductionmentioning
confidence: 99%
“… 17 , 18 Nonetheless, one of the major challenges associated with PIT is limited photosensitizer delivery to cancer cells. 18 , 19 , 20 This can be attributed to several factors including finite antigen numbers per cancer cell, limited number of photosensitizer-to-antibody payload, and poor tumor accessibility of antibodies. 20 This study overcomes this limitation through the rigorous examination of transient flow as a drug delivery platform to enhance total cellular PIC delivery and thereby bolster cytotoxic effects.…”
Section: Introductionmentioning
confidence: 99%